A systematic review of silymarin and silibinin mechanisms for attenuating cerebral ischemia-reperfusion injuries - Hossein Mardani-Nafchi; Saeid Heidari-Soureshjani; Sahar Rostamian (Avicenna Journal of Phytomedicine)
Objective: Cerebral ischemia-reperfusion injury (CI/RI) can lead to a range of impairments and even permanent disability.. This systematic review was designed to comprehensively investigate the biological effects of silymarin and silibinin in mitigating CI/RI.Materials and Methods: To find studies published before January 02, 2024, a comprehensive electronic search was carried out across multiple databases, including Cochrane Library, PubMed, Embase, Web of Science, and Scopus. Data including study characteristics, methods, and biological mechanisms were extracted.Results: Silymarin and silibinin potentially improved endogenous antioxidants and reduced lipid peroxidation, nitric oxide (NO), and malondialdehyde (MDA) levels. They also enhances the nuclear factor erythroid 2-related factor 2 (Nrf2) expression and upregulated HO-1 and NAD(P)H: quinone oxidoreductase 1 (NQO1). They also protected the activity of Na+–K+ ATPase, activating mitochondrial membrane potential that suppresses mitochondrial permeability transition pores (mPTP). Moreover, they upregulated proliferator-activated receptor gamma coactivator 1-alpha (PGC1-α), uncoupling protein 2 (UCP2), nuclear respiratory factor 1 (NRF1), and reduced inducible-NO synthase (iNOS), cyclooxygenase-2 (COX-2), and myeloperoxidase (MPO) expression. They inhibited transcription factors, including nuclear factor-kappa B (NF-κB) and IκB-α degradation. They also attenuated tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and IL-6. Anti-apoptotic properties were revealed by increasing protein Bcl-2 and reducing p53, Bax, caspase-3, and 9 expressions. silymarin improves pathological changes, behavioral tests, and decreases cerebral infarct size.Conclusion: Silymarin and silibinin indicated promising effects on CI/RI through various mechanisms. However, well-designed clinical trials are needed to validate these findings in human subjects.